Chediak Higashi Syndrome – Too little, too late? - Mehmood, Yasar; Khan, Shahtaj; Wahid, Quratul Ain; Paracha, Imran; Ali, Asif; Ahmad, Nasir; -Raziq, Fazl-e (International Journal of Pathology, 2018)
Introduction: Chediak-Higashi syndrome (CHS) is a rare multi-system disorder resulting from mutations in theLysosomal Trafficking Regulator Protein (LYST) gene. The resultant dysfunctional vesicular transport causesseverely disturbed cellular functions such as phagocytosis and lysosomal trafficking. Clinically, affected patientspresent with recurrent pyogenic infections, partial albinism and peripheral neuropathies. Disease onset is usuallyin the first year of life however, late presentations have been reported. Presence of giant neutrophilic granules inblood smears provide the first clues to diagnosis. Bone marrow transplant improves the immune deficiency. Inresource deprived countries, antibiotic prophylaxis and genetic counselling remains the only option.Materials and Methods: We report 8 cases diagnosed with CHS between 2008 and 2016 in two tertiary carehospitals of Peshawar. Complete history and physical examination was performed. In addition, microscopicexamination of Giemsa stained peripheral blood and bone marrow smears was performed. Myeloperoxidasestaining was performed on blood and bone marrow smears.Results: The mean age of patients at diagnosis was 36 months (range 3 months – 10 years). Main presentingfeatures were a history of recurrent chest and skin abscesses. All patients had variable degrees of oculocutaneousalbinism and silvery grey hair. Six patients had one or more siblings with similar symptoms or death duringinfancy or early childhood. All patients fulfilled the criteria for ‘accelerated phase’ of CHS at diagnosis.Cytopenias in peripheral blood and hemophagocytosis was invariably present in all patients. Myeloperoxidasestaining of the blood and bone marrow smears showed large peroxidase positive granules in mainly myeloidcells. Supportive therapy such as prophylactic antibiotics and high dose vitamin C were prescribed and patientswere discharged after the acute episodes. No follow-up was performed.Conclusion: CHS patients were diagnosed based on clinical presentation and peripheral blood and bonemarrow findings of large myeloperoxidase positive granules in myeloid cells. Most of these patients had beenadmitted in hospitals before but were not diagnosed on first admission. The majority of cases presented inaccelerated phase, were discharged without family testing, genetic counselling or bone marrow transplant. Inconclusion, a high-degree of suspicion is necessary for the diagnosis of rare diseases such as CHS. Furthermore, apro-active concerted approach by the hematologists and pediatricians is of paramount importance to offer theavailable treatment options and genetic counselling.